UJI MULTI STAGE PENGARUH KARAKTERISTIK PERSONAL AUDITOR TERHADAP KUALITAS AUDIT MELALUI PERILAKU DYSFUNGSIONAL AUDIT DENGAN PENDEKATAN KEPUTUSAN BERBASIS ETIS (Studi Kasus Pada KAP di Sumatera Bagian Tengah) - -, Srini; DP, Emrinaldi Nur; Ali, Al Azhar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
Auditing process often encounter problems due to the number of auditors who violate professional standards of auditors and the code ethics of public accountants in the audit process, thereby reducing the quality of audits produced. The purpose of this study was to examine the influence of personal auditors characteristics on audit quality through dysfungsional audit behavior-based approach ethical decision. ethically-based decisions.This study uses a saturated sampling method to choosed sample. The sample in this study is the auditor who works in Public Accounting Firm (KAP) in the central part of Sumatra (Pekanbaru, Padang, Batam and Jambi) with 52 sample auditors. The data used in this study are primary data questionnaire submitted directly to the auditor by the researcher. Data were analyzed using PLS program version 2.0.M3.Hypothesis testing using Partial Least Square showed variable results of work stress, cognitive moral development, moral evaluation deontological and teleological, Machiavellian nature of a significant effect on audit quality and the variable of the dysfungsional audit behavior no significant. While work stress variables, moral evluation deontological and teleological significant effect on the dysfungsional audit behavior and the dysfungsional nature mchiavellian not significant to dysfungsional audit behavior. While the work stress variables, Machiavellian nature, and moral evaluation deontological and teleological have significant effect on audit quality mediated by dysfungsional audit behaviors .Keywords: audit quality, Personal Characteristics Auditors, and dysfungsional audit behavior.